Relationship of exercise test variables to cycling performance in an Ironman triathlon - Laursen, P. B.; Rhodes, E. C.; Langill, R. H.; McKenzie, D. C.; Taunton, J. E. (European Journal of Applied Physiology, 2002)
The purpose of this study was, firstly, to investigate the intensity of exercise performanceof highly trained ultra-endurance triathletes during the cycling portion of an Ironman triathlon, and, secondly, to examine the anaerobic threshold and its relationship to this performance. Following a peak oxygen consumption (O2peak) test on a cycle ergometer to determine the heart rate (HRTh,vent) and power output (POTh,vent) at the ventilatory threshold (Thvent), 11 highly trained male triathletes [mean (SEM) age 35.8 (1.6) years, body fat 11.7 (1.2)%. O2peak 67.5 (1.0) ml·kg-1·min-1] who were participating in an Ironman triathlon, in random order: (1) cycled at their POTh,vent (BiTh,vent) until they were exhausted, and (2) cycled for 5 h at a self-selected intensity (BiSSI). Cycling power output (PO), oxygen uptake (O2), heart rate (HR) and blood lactate concentration ([La-]b) were recorded at regular intervals during these trials, while performance HR was recorded during the cycling phase of the Ironman triathlon. Significantly greater (P<0.05) values were attained during BiTh,vent than during BiSSI for PO [274 (9) compared to 188 (9) W], O2 [3.61 (0.15) compared to 2.64 (0.09) l·min-1], and [La-]b [6.7 (0.8) compared to 2.8 (0.4) mmol·l-1]. Moreover, mean HR during the Ironman triathlon cycle phase [146.3 (2.4) beats·min-1; n=7] was significantly greater than mean HR during BiSSI [130 (4) beats·min-1], and significantly less than mean HR during BiTh,vent [159 (3) beats·min-1; all P<0.05]. However, HR during the cycle portion of the Ironman triathlon was highly related to (r=0.873; P<0.05) and not significantly different to HRTh,vent [150 (4) beats·min-1]. These data suggest that ultra-endurance triathletes cycle during the Ironman triathlon at a HR intensity that approximates to HRTh,vent, but at a PO that is significantly below POTh,vent.